Association of dexmedetomidine with recovery room and hospital discharge times: A retrospective cohort analysis. Issue 11 (2nd August 2021) - West, Nicholas; Görges, Matthias; Poznikoff, Andrew; Whyte, Simon; Malherbe, Stephan
Abstract: Background: Dexmedetomidine is a useful anesthetic adjunct, increasingly popular during pediatric surgery and procedural sedation. Its half‐life of 2–3 hours might prolong recovery and discharge times when compared with an un‐supplemented propofol anesthetic. This may create an additional burden in a busy post‐anesthetic care unit (PACU). Aim: To investigate whether intraoperative adjuvant dexmedetomidine delays PACU discharge in patients undergoing propofol anesthesia for day surgery or procedural investigations with minimal anticipated post‐procedural pain. Methods: We conducted a retrospective review of outpatient procedures performed during a six‐month period including pediatric patients, ASA physical status I‐III, who underwent intravenous anesthesia with propofol and remifentanil for magnetic resonance imaging (MRI), strabismus repair, upper gastrointestinal endoscopy, or combined upper/lower gastrointestinal endoscopy. Patients receiving a sedative premedication, long‐acting opioids, or volatile anesthetics for maintenance of anesthesia, were excluded. Duration of PACU stay was compared for patients who did or did not receive intraoperative dexmedetomidine in the four procedure groups. Results: Charts were reviewed for 359 patients; 130 (36%) received dexmedetomidine. Median differences in duration of PACU stay for dexmedetomidine versus non‐dexmedetomidine cases were: 5 minutes (95%CI 0 to 10, p =0.037) for MRI; 5 minutes (95%CI −3 to 15, p =0.258) for strabismus surgery; 7 minutes (95%CI 3 to 10, p <0.001) for upper endoscopy; and 5 minutes (95%CI 1 to 12, p =0.021) for combined upper/lower endoscopy. Linear regression (F=61.1, adjusted R 2 =0.40) indicated a significant relationship between dexmedetomidine dose (estimate 14.6 minutes per μg/kg, 95%CI 8.2 to 21.1, p <0.001) and duration of PACU stay. Conclusion: We found evidence for a small association of intraoperative dexmedetomidine with duration of recovery from propofol anesthesia for a set of common outpatient procedures, with a potential dose relationship equivalent to approximately 15 minutes delay per μg/kg dexmedetomidine administered. Future research into the benefits of dexmedetomidine in pediatric anesthesia should further evaluate this relationship.